هرمنيوطيقا قضايا العقيدة في الفكر العربي الحديث: دراسة تحليليّة: Hermeneutics of Creed’s Issues in the Modern Arab Thought: An Analytical Study - al-Ajmi, Abdullah Awad (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
The term ‘hermeneutics’ appears in Western thought when they seek the right method to understand and interacting with the text. Some Arab thinkers believe this method as the only approach to understand Shariah texts and religious matters while at the same time seen in line with rational thinking and empirical science. This study is aimed at explaining the modern Arabic thinking regarding hermeneutics and their efforts to apply this method to Shariah texts as well as basic beliefs such as divine, prophecy and metaphysical aspects that are not reachable to the mind as found in the Qur’an and the Hadith.